Some remarks about a simple history dependent nonlinear viscoelastic model. (September 2015) - Pucci, Edvige; Saccomandi, Giuseppe
Abstract : Highlights: We consider a nonlinear viscoelastic model of history type. We examine creep and recovery phenomena. We consider traveling waves propagation. We obtain closed form and analytical results. We discuss the relevance of our findings in the framework of the modeling of natural rubber. Abstract: A simple model for history dependent nonlinear viscoelasticity is considered. The determining equation governing shear motions is derived and investigated in the quasistatic approximation and under the traveling waves ansatz. Traveling waves are possible only if an inequality involving the constitutive parameters is satisfied. This fact is in contrast to what happens in viscoelasticity of the Kelvin–Voigt type. On the other hand, in the quasi-static approximation (classical creep and recovery experiments) the behavior of the history dependent model is similar to analogous rate dependent models.